Visual value clarification â€ A method for an effective brief - SÃ¸ren Wandahl (Journal of Civil Engineering and Management, 2004)
The purpose of this research is to explore the processes in the conception of construction projects, ie the brief. More specifically, the intention is to discuss how it can be ensured that the client receives the right product, ie that the real and justified needs of the client and the users are captured, and that they through an iterative process are transformed into building requirements. The research is carried out by a literature study on the briefing process. This reveals that today's briefing process is far from perfect, and a lot of challenges exist. It is when discussed which factors influence the effective briefing process, and a method to facilitate this is proposed. The visual value clarification method is a simple method for supporting the client and the project team in the briefing process. It should help the client recognise his real needs, create a better communication and give the project team a better understanding of the client's needs.